The other side of the coin: oxytocin decreases the adherence to fairness norms - Radke, Sina; De Bruijn, Ellen R. (Frontiers in Human Neuroscience, 2012)
Oxytocin has been implicated in prosocial behaviors such as trust and generosity. Yet, these effects appear to strongly depend on characteristics of the situation and the people with whom we interact or make decisions. Norms and rules can facilitate and guide our actions, with fairness being a particularly salient and fundamental norm. The current study investigated the effects of intranasal oxytocin administration on fairness considerations in social decision-making in a double‐blind, placebo‐controlled within‐subject design. After having received 24 IU of oxytocin or placebo, participants completed a one‐shot Dictator Game and played the role of the responder in a modified version of the Ultimatum Game, in which an unfair offer of 8 coins for the proposer and 2 coins for the responder is paired with either a fair‐ (5:5) or no‐alternative (8:2). Rejection rates were higher when a fair alternative had been available than when there was no alternative to an unfair offer. Importantly, oxytocin did not de- or increase rejection rates overall, but reduced the sensitivity to contextual fairness, i.e. the context of alternatives in which an offer was made. As dictators, participants allocated less coins to the recipient when given oxytocin than when given placebo, indicating a decline in generosity. These results suggest that oxytocin decreases the adherence to fairness norms in social settings where others are likely to be perceived as not belonging to one’s ingroup. While our findings do not support the prosocial conception of oxytocin, they corroborate recent ideas that the effects of oxytocin are more nuanced than assumed in the past.